Evaluation of ELF Procedure for Seismically Isolated Buildings Under Extreme Earthquakes: Near-Field Effects - Yenidogan, Cem; Mert, Aydin (MDPI, 2026)
The earthquake doublet on 6 February 2023 served as an important test in T & uuml;rkiye. It helped assess the vulnerability of T & uuml;rkiye's building stock under different seismic loading conditions across a large region. The widespread destruction and casualties observed in heavily damaged cities following the 6 February 2023 earthquakes served as a warning. This urged a re-evaluation of the seismic performance assessment framework and risk mitigation strategies. Seismic isolation technology is considered the best method for earthquake-resilient design. Passive control systems are primarily preferred for use in critical facilities, such as healthcare complexes and data centers. Properly designed seismically isolated hospital buildings exhibited superior performance during the 6 February 2023 earthquakes compared to fixed-base counterparts. However, their use in residential buildings in T & uuml;rkiye is still limited due to impediments such as stringent code requirements and peer review processes. This study evaluates the effectiveness of the ELF procedure in the Turkish Seismic Design Code-2018, incorporating two site-specific studies and earthquake record scaling in Antakya city center. Moreover, it examines the influence of considering directivity effects for using seismic isolation systems in regions with high seismicity. An effective and rapid evaluation procedure is employed for the inelastic response of seismically isolated residential buildings in accordance with the TSDC-2018 without needing any particular academic or commercial software. A suite of differential equations using the design parameters is arranged to represent the overall dynamics of seismically isolated buildings. Disregarding the directivity effects in site-specific studies for the selected construction site in Antakya city center can result in large earthquake demands and careful attention should be given to reconstruction studies for urban planning and more detailed studies should be carried out including other complex mechanisms experienced during the 6 February 2023 T & uuml;rkiye earthquake doublet.
Keywords: seismic isolation; TSDC-2018; selection and scaling of ground motions; extreme earthquakes; ELF procedure; site-specific hazard study; Bouc-Wen oscillator; near-field effects; directivity; seismic hazard; AVERAGE HORIZONTAL COMPONENT; GROUND-MOTION; PREDICTION; BEHAVIOR; PERIODS; DESIGN; MODEL; PGV; Construction & Building Technology; Engineering